New clues concerning pigment biosynthesis in green colored fiber provided by proteomics-based analysis - Yan-jun LI; Shi-chao SUN; Xin-yu ZHANG; Xiang-fei WANG; Yong-chang LIU; Fei XUE; Jie SUN (Journal of Integrative Agriculture, 2018)
To separate the proteins related to pigment synthesis in green colored fiber (GCF), we performed a comparative proteomic analysis to identify the differentially expressed proteins between green cotton fiber and a white near-isogenic line (NIL). One differential spot identified as phenylocumaran benzylic ether redutase-like protein (PCBER) was expressed only in GCF, but was not found in white colored fiber (WCF) at any time points. Since PCBER was a key enzyme in lignans biosynthesis, total lignans were extracted from GCF and WCF and their content was determined by using a chromotropic acid spectrophotometric method. The results showed that total lignans content in GCF was significantly higher than that in WCF. The qPCR analysis for two PLR genes associated with lignans biosynthesis showed that the expression level of two genes was much higher in GCF than that in WCF at 24 and 27 days post anthesis (DPA), which may be responsible for the higher lignans content in GCF. Our study suggested that PCBER and lignans may be responsible for the color difference between GCF and WCF. Additionally, p-dimethylaminocinnamaldehyde (DMACA) staining demonstrated that the pigment in GCF was not proanthocyanidins, and was different from that in brown colored fiber (BCF). This study provided new clues for uncovering the molecular mechanisms related to pigment biosynthesis in GCF.